Rebranding And Digitalization As Drivers Of Sme Growth: Evidence From Baso Prapatan, Cikidang Village - Itto Turyandi; Muhammad Rafi S; Rizky Zakaria; Arvan Putra Maulana S; Muhammad Azis Pasha N; Abdul Malik Rahman Kasim; Yundha Destianty; Dela Nawa Aprilianti; Maisa Nidalatifah; Silvi Adriyani W; Dzysmi Nurani Fatimah1 (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract Small and Medium Enterprises (SMEs) face persistent barriers such as limited branding capacity, low digital literacy, and restricted market access, which threaten their sustainability in rural contexts. This study aims to analyze the role of rebranding and digitalization in enhancing SME growth, with evidence from Baso Prapatan in Cikidang Village. The research employs the Theory of Planned Behavior, Resource-Based View, and Innovation Diffusion Theory as theoretical frameworks. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation, and analyzed with Miles and Huberman’s interactive model. The findings show that rebranding through the creation of a new logo and promotional banner significantly improved the SME’s identity and credibility, while digitalization via social media and Google Maps expanded market visibility and consumer engagement. The study highlights that even low-cost interventions can strengthen competitiveness and contribute to rural economic development. Keywords: Rebranding, Digitalization, SMEs